Gender-based Students’ Listening Ability of Auditory Learning Modality - Cunandar, Dadang (LPPM Universitas Advent Indonesia, 2020)
This study aims to determine the characteristics of gender-based auditory learning modality, supporting aspects of listening ability, and gender-based listening abilities. This study used a qualitative approach with a case study design. The research subjects were the fifth grade students of Cigugur State Elementary School. Data was collected through literature studies, observations, interviews, documentation, and field notes. The validity of the data is checked by data credibility and data dependability. Data is analyzed by data reduction, data presentation, and conclusion or verification. The results of the study show 85% students showed the characteristics of auditory learning modality. The characteristics of male students tend to be independent, strong, and ambitious while female students are more cheerful, spoiled and obey. The supporting aspects of listening ability are physical aspect, psychological aspect, sex, and learning media. The listening ability of female students is better than male.